Fixed point theory and applications - Agarwal, Ravi P. (Cambridge University Press, 2001)
This book provides a clear exposition of the flourishing field of fixed point theory and explores many applications of the theory to analysis, with topological considerations playing a crucial role. The very extensive bibliography and close to 100 exercises